Facing Career Challenges in the Digital Era: Career Education and Guidance Program through Instagram Live Talkshow for Accounting Students - Renna Magdalena; Ilyona Risty; Go George Herbert; Felicia Juliani Leliga; R. Bernardinus Chrisdianto; Jessica Jaury; David Welson Susanto (Universitas Pelita Harapan, 2024)
Facing career challenges in the digital era is crucial for accounting students to prepare for and compete in an increasingly competitive job market. This topic was selected to guide and educate accounting students on strategies to tackle career challenges through the IG Live program. This program helps students understand the various career paths, develop soft skills and leverage technology in career guidance. The community service method employed is the organization of interactive and educational IG Live sessions. These sessions include vital components such as discussions with experienced speakers from the accounting industry, successful alums, and faculty members, offering practical insights into accounting careers. Additionally, participants are encouraged to engage in interactive Q&A sessions and receive supporting materials such as career guides and articles. This activity will enhance career knowledge, build the necessary skills, and strengthen students' professional networks, thus making them more prepared and confident in facing the job market after graduation.